Assessing the impact of an antigen-specific antibody response on atherosclerosis development in mice - Del Monte-Monge, Alberto; Martos-Folgado, Inmaculada; Rodríguez-Ronchel, Ana; Ramiro, Almudena R. (STAR protocols, 2023)
The antibody immune response plays a critical role in atherosclerosis. Here, we present a protocol for assessing the impact of an antigen-specific germinal center antibody response on atherosclerosis development, using a pro-atherogenic mouse model deficient for the production of germinal-center-derived antibodies. We describe steps for bone marrow transfer from donor mice into irradiated recipient mice. We then detail immunization of mouse chimeras with atheroprotective malondialdehyde low-density lipoprotein during high-fat diet feeding and atherosclerosis burden analysis. For complete details on the use and execution of this protocol, please refer to Martos-Folgado et al. (2022).1 [Display omitted] •Detailed protocol to generate Ldlr−/−Prdm1fl/flAicda-Cre+/ki bone marrow chimeras•Detailed instructions of MDA-LDL immunization during atherosclerosis induction•Extraction and processing of mouse hearts for the study of atherosclerosis•Quantification of atherosclerosis in MDA-LDL-immunized Prdm1fl/flAicda-Cre+/ki mice Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics. The antibody immune response plays a critical role in atherosclerosis. Here, we present a protocol for assessing the impact of an antigen-specific germinal center antibody response on atherosclerosis development, using a pro-atherogenic mouse model deficient for the production of germinal-center-derived antibodies. We describe steps for bone marrow transfer from donor mice into irradiated recipient mice. We then detail immunization of mouse chimeras with atheroprotective malondialdehyde low-density lipoprotein during high-fat diet feeding and atherosclerosis burden analysis.